2020
DOI: 10.1007/s10266-020-00539-3
|View full text |Cite
|
Sign up to set email alerts
|

One-year clinical performance of lithium disilicate versus resin composite CAD/CAM onlays

Abstract: To compare the 1-year clinical performance of lithium disilicate and resin composite CAD/CAM onlay restorations. Twenty patients that required two restorations in posterior teeth, with at least one cusp to be covered, received two onlays. One was made with IPS e.max CAD (Ivoclar-Vivadent) and the other with Lava Ultimate (3M Oral Care). Two blind observers evaluated the restorations at baseline and 1 year after the onlays were cemented, according to FDI criteria. At each recall, digital photographs, bite-wing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 60 publications
6
27
1
Order By: Relevance
“…The clinical performance of Lava Ultimate restorations has previously been studied using either the USPHS [37] or FDI criteria [35,36,39,52]. The USPHS criteria used in this study do not fully comply with the modified set proposed by Fasbinder et al [37], who added extra subset scores for most of the criteria except for color match and anatomic form.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The clinical performance of Lava Ultimate restorations has previously been studied using either the USPHS [37] or FDI criteria [35,36,39,52]. The USPHS criteria used in this study do not fully comply with the modified set proposed by Fasbinder et al [37], who added extra subset scores for most of the criteria except for color match and anatomic form.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Zimmerman et al [39], 13% of restorations mimicked the adjacent tooth color, and 87% showed acceptable minor or clear discrepancies in color match. Souza et al [35] assigned a good color match to 25% of Lava Ultimate restorations and a minor or distinct but acceptable color deviation with the adjacent tooth structure to 75%, which was better than the IPS e-max CAD onlays in a split-mouth design. Only Fasbinder et al [37] reported an almost ideal (93%) match between tooth and restoration after 5 years, which was comparable to leucite reinforced ceramic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations